Coagulopathy in COVID-19: A Systematic Review - Winata, Sharleen; Kurniawan, Andree (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Introduction: Corona Virus Disease 2019 (COVID-19) firstly appeared in Wuhan, China in December 2019 and defined as a pandemic in March 2020. COVID-19 divided into asymptomatic, mild, and severe symptoms. Coagulopathy may have happened in severe COVID-19 infection, it was also associated with high mortality in COVID-19 patients. Laboratory examination is the main protocol to identify coagulopathy, thereby it also determined the prognosis of COVID-19 patients with coagulopathy. Here, we review the current evidence describing the mechanism, diagnosis, treatment, and mortality of coagulopathy in COVID-19.Method: We identify 8 studies and/or review articles evaluating coagulopathy in COVID-19 patients by searching PubMed and EMBASE databases.Results: DIC is most commonly found in death with COVID-19, the risk of VTE also higher in severe COVID-19 because of immobility and long-term bed rest. Sepsis-induced DIC is associated with organ dysfunction as in the patient with viral infection as in COVID-19 infection. Sepsis-induce Coagulopathy (SIC) score, D-dimer, and prothrombin time (PT) measured at the time the patient classified as severe COVID-19. Higher D-dimer and FDP levels, longer PT and activated partial thromboplastin time (APTT) may have a poor prognosis. Treatment with Low Molecular Weight Heparin (LMWH) effective to reduced 28-day mortality in patients with SIC ≥ 4 and D-dimer > six-fold of the upper limit of normal. Conclusion: Coagulopathy plays a big role to determine the prognosis of COVID-19 patients. Treatment with LMWH may give some benefits to COVID-19 patients.